Cryptanalysis and Improvement of an Efficient and Secure Medical Image Protection Scheme. (22nd February 2015) - Zhang, Li-bo; Zhu, Zhi-liang; Yang, Ben-qiang; Liu, Wen-yuan; Zhu, Hong-feng; Zou, Ming-yu
Abstract : Nowadays, the increasing demand for telemedicine services has raised interest in the real-time medical image protection literatures. In this paper, we evaluate the security of an efficient and secure medical image protection scheme recently proposed (Fu et al., 2013). It is found that this scheme can be successfully broken by launching chosen-plaintext attacks. Improvement is subsequently developed for promoting the security and efficiency performance. Extensive security analyses and experimental results both indicate that the improved scheme can well address the security flaws and advance the speed performance of the original one.